Designing the content of religious education learning in creating sustainability among children with learning disabilities: A fuzzy delphi analysis - Zulkifli, Hafizhah; Rashid, Syar Meeze Mohd; Mohamed, Suziyani; Toran, Hasnah; Raus, Norakyairee Mohd; Pisol, Mohd Izzuddin Mohd; Suratman, Muhamad Nasri (Frontiers in Psychology, 2022)
Teachers found it is hard to figure out what are the best approach and strategies shall be employed to create an effective learning activity that can benefit the children. Children with disabilities have distinctive learning difficulties, depending on each individual. Therefore, this requires modification and adaptation in the learning activities to make sure they can learn effectively. Teachers need to make adjustment to the instructions, learning materials, assessments, and activities to accommodate the children with disabilities. Therefore, the objective of this research is to develop the content of religious educcation for children with disabilities using fuzzy delphi. This research used method of design and developmental research approach which have three phases. In this research, the researchers focus on the second phase of fuzzy delphi. There were 20 panel experts involved in this research to rank the elements in developing religious education model. Findings showed that, all the elements such as learning style, rights of disabled people, manners and universal design were above 70% that considered suitable and applicable. It is hoped that this model can assist and guide teachers in teaching religious education for children with disabilities.